Adaptation a un environnement en mutation: Accords et dissensions dans le secteur de l’enseignement postsecondaire quebecois - Crespo, Manuel; Hache, Jean B. (Canadian Journal of Higher Education, 1990)
Fiscal restraint has prompted an urgent examination of the policy of democratization of post-secondary educational institutions, of the adequacy of their programs in light of market needs, and of their dependence of state funding. This study describes, from the administrators’ perspective, the areas of agreement and disagreement in the choices faced by both French and English language post-secondary institutions in Quebec. Administrators of these institutions concur on objectives for adapting to the environment. However, CEGEP officials, contrary to the direction taken by universities administrators, are pursuing their objectives by adhering more closely to government priorities and by liberalizing admission policies. Some differences in the choices made by institutions appear to be based on the language of the institution. generally, the analyses based on the variables of sex, age, and education were not significant. The article concludes with a discussion of the possible consequences of the institutional choices.